Effect of ammonium molybdate on the quality of feijoa fruits - Reyes-Ramos, Denis; Ayala-Arreola , Juan; Colinas-León, María Teresa Beryl; Cruz-Alvarez, Oscar; Ojeda-Barrios, Dámaris Leopoldina; Martínez-Damián, María Teresa (Revista Mexicana de Ciencias Agrícolas, 2025)
Molybdenum is an essential micronutrient that is involved in several enzymes, including nitrate reductase. This trial aimed to evaluate the physicochemical quality and the pectin methylesterase activity in fruits from feijoa trees sprayed with 0, 100, 200, and 300 mg L-1 of ammonium molybdate. To this end, an experiment was set up in 2023 in a completely randomized block design with three replications. Spraying 200 mg L-1 of ammonium molybdate increased the weight and firmness of the fruits. It was found that the pulp and skin of fruits harvested from trees treated with 100 mg L-1 showed lower vitamin C content, with values of 0.33 and 0.55 mg g-1, respectively. The application of molybdenum increased the content of total phenols in the pulp, with values that fluctuated between 3.72 and 3.66 mg g-1. Nonetheless, only the doses of 100 and 200 mg L-1 affected the values for this secondary metabolite in the skin. Only an increase in antioxidant capacity was observed for the pulp, where the dose of 300 mg L-1 was similar to the control. The pulp and skin of the fruits evaluated decreased their total sugar content and the levels of pectin methylesterase activity. Molybdenum foliar spraying can be a viable alternative to improve the size, firmness, and phenol content in the fruit pulp, parameters widely valued in harvest quality and during postharvest handling and that give high nutritional value to feijoa fruit.
Keywords: Acca sellowiana; bioactive compounds; plant nutrition